Successful revascularisation following delayed presentation of bilateral renal artery thrombosis after blunt abdominal trauma. (April 2014) - Sawant, Ajit; Kumar, Vikash; Bhalerao, Sagar; Badne, Avinash
Traumatic blunt abdominal bilateral renal artery thrombosis is a rare entity leading to end stage renal disease and has significant morbidity due to renal replacement therapy. Previously many attempts of revascularisation beyond 24 h have led to failure. We report a case of delayed presentation of bilateral renal artery thrombosis in which revascularisation was attempted beyond 24 h and was successful in terms of patient becoming dialysis-free.